Safety First? Exploring Occupational Health and Safety Knowledge Levels of Chemistry Education Students in Laboratory Settings - Ghalby, Agia; Malaluan, Lloyd Arvin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The main objective of this study is to identify students' knowledge of Occupational Safety and Security. Methodology: One hundred and eighty three (183) students of the Chemistry Education study program, Faculty of Tarbiyah and Teacher Training, Syarif Hidayatullah State Islamic University, Jakarta, participated in answering the test on Occupational Safety and Security. This test was developed based on three Occupational Safety and Security indicators, namely storing, general work procedures (handling), and disposal of hazardous chemicals. Main Findings: Based on data analysis, it was found that on average students have insufficient knowledge about the three Occupational Safety and Security indicators (38%). In detail, the indicator for storing is 33%, general work procedures is 34%, and the last is for disposing of hazardous chemicals is 47%. The results obtained have not been able to show students' general knowledge about Occupational Safety and Security, but can be an early warning to realize the importance of Occupational Safety and Security knowledge for students when experimenting in a chemistry laboratory. Novelty/Originality of this study: This study examines the level of knowledge of Chemistry Education students regarding the principles of (Occupational Safety and Security) in the laboratory, which is an innovative step in increasing awareness and implementation of safety protocols in practical learning.